Beroespkeuses van studente - Slabbert, F. van Zyl (Frederik van Zyl), 1940-2010 (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MA (Sociology and Social Anthropology))--University of Stellenbosch, 1964.